A Prospective Study to Evaluate Effectiveness of a Tinnitus Relief Device in a Clinical Setup - Aggarwal, Nitin; Gupta, Soniya; Goyal, Prashant (Annals of Otology and Neurotology, 2019)
Introduction Tinnitus has been shown to decrease the quality of life of a person. Being a less understood domain of the medical field, there are no definitive established therapies that can be applied to all patients of tinnitus. The current study is an effort to evaluate the effectiveness of the Tinnitus Relief device in the patients of tinnitus.Aim To evaluate the effectiveness of Tinnitus Relief device TRx in treatment of tinnitus.Methods A prospective study involving 67 participants suffering from tinnitus was conducted in a clinical setup at Delhi, Chandigarh, and Mumbai. These participants were subjected to pure tone audiometry (PTA) and an interview using Tinnitus Handicap Inventory (THI) questionnaire. These participants were advised to use Tinnitus Relief device TR201, TR301, TR401 for more than 6 to 10 months. Improvement in tinnitus in terms of percentage, questions pertaining to THI, and overall improvement in life (subjective) were evaluated after discontinuation of the use of the device in each participant.Results It was found that there was significant improvement in mean THI score, following treatment with Tinnitus Relief TRx. This device was also able to completely alleviate 5 out of 12 associated complaints of tinnitus. No association could be found between the use of Tinnitus Relief therapy and hearing loss.Conclusion Tinnitus Relief TRx can emerge as an effective tool for treatment of the tinnitus and can improve the life of the sufferer.
Keywords: Tinnitus Relief device; tinnitus; Tinnitus Handicap Inventory; effectiveness